(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Confessional poetry can be broke down as an expansion of the continuous flow method created and altered by present day writers. It is a part of present day poetry there is no spot either for religion or morals in this poetry. Her poetry is concerned both with the outside and inside world. Confessional comprises an intriguing component of women’s composition, in which the poets reveal confidentialities that bond her private and open circles together. This paper is an examination concerning the poetry of Kamala Das (1934-2009), the productive Indian lady essayist of the twentieth century to explain confessional components in her poetry. Das obtains this style of composing from her contemporary American writers and utilizes it as a methods for verbalization, exchange and obstruction through anticipating oneself.